A promising recovery housing model for American Indian communities. Issue 8 (2nd September 2019) - Jason, Leonard A.; Kassanits, Jessica; Reilly, Angela; Bobak, Ted; Guerrero, Mayra; Stevens, Ed; Light, John M.; Doogan, Nathan J.
Abstract: In 2016, two Oxford House (OH) recovery homes were established for the Suquamish Tribal reservation. A group of researchers interviewed house members and key individuals responsible for the creation of these two unique OHs. Because American Indians are an at‐risk population for substance use disorders, our study explored whether an OH‐type recovery home model could be successfully adapted to this population, given the specific nature of tribal cultures. Findings indicated that the residents, composed of both American Indians and non‐American Indians, found these OHs to be supportive of recovery in general and with the values of American Indians. The tribal community's positive attitudes toward these recovery homes may have been due to similarities between the Suquamish Tribal Government and OH's democratic structures, with all individuals having a voice in the decision making process. The overall findings suggest that these types of culturally modified recovery settings on American Indian tribal lands could be an important resource for individuals dealing with substance use disorders.